Complete mitochondrial genome of the Ptychobarbus chungtienensis (Teleostei: Cyprinidae) - Qiu, Yuping (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome of Ptychobarbus chungtienensis was first determined by using a PCR-based sequencing method. Its mitochondrial genome is 16,970bp in length, consisting of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a non-coding control region, and its gene order was consistent with other fishes. In the control region, there was a 54 bp tandem repeat array identified at 3′ end. Phylogenetic analysis showed that P. chungtiensensis was clustered with other three species of Ptychobarbus.